1999
DOI: 10.1620/tjem.187.15
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MEF2 Genes during Human Cardiac Development.

Abstract: To better understand the regulatory mechanisms in gene expression of human cardiomyocytes, we studied the expression of MEF2 genes encoding transcription factors during the course of cardiac development. Expression of all four MEF2 transcripts (MEF2A, MEF2B, MEF2C, and MEF2D) were detected in all developmental stage of the human heart, while Mef2b transcripts were down-regulated in mouse heart development. Although none of the MEF2 genes, besides mouse Mef2b, exhibited any remarkable quantitative change in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…2B). These motifs resemble the binding specificity of TFs in the families of LMO2, MEF2, ETS, and SP1-transcription factors known to play roles in heart development (Iida et al 1999;Flesch 2001;Zhu et al 2005;Pham et al 2007;Gratzinger et al 2009). The fact that these novel motifs were chosen in addition to the database motifs can be explained by one of the three scenarios: (1) specificities of the TFs binding the database motifs may not have been characterized precisely; (2) these motifs could be recognized by novel TFs, the specificities of which have not been characterized so far; or (3) the database TFs, specificities of which are characterized using in vitro methods, may have slightly different specificities in the heart due to various cofactors in vivo.…”
Section: Selected Features Have Been Previously Implicated In Heart Dmentioning
confidence: 90%
“…2B). These motifs resemble the binding specificity of TFs in the families of LMO2, MEF2, ETS, and SP1-transcription factors known to play roles in heart development (Iida et al 1999;Flesch 2001;Zhu et al 2005;Pham et al 2007;Gratzinger et al 2009). The fact that these novel motifs were chosen in addition to the database motifs can be explained by one of the three scenarios: (1) specificities of the TFs binding the database motifs may not have been characterized precisely; (2) these motifs could be recognized by novel TFs, the specificities of which have not been characterized so far; or (3) the database TFs, specificities of which are characterized using in vitro methods, may have slightly different specificities in the heart due to various cofactors in vivo.…”
Section: Selected Features Have Been Previously Implicated In Heart Dmentioning
confidence: 90%
“…The full dynamics of MEF2 isoform expression is outside the scope of this review and may be found elsewhere (Desjardins & Naya, 2016). Nevertheless, we summarize by noting that expression of individual isoforms of MEF2 initiates between e7.5 and e8.5 in mice; postnatally, MEF2A, MEF2C and MEF2D are expressed (Iida et al 1999). In the perinatal period, these MEF2 isoforms may have non-overlapping and even potentially antagonistic function (Desjardins & Naya, 2017).…”
Section: Mef2 Familymentioning
confidence: 99%
“…Furthermore, in mice ablation of Mef2c in the anterior second heart field causes outflow tract defects, such as overriding aorta, double outlet right ventricle and transposition of the great arteries 92 . In humans, all four MEF2 transcript variants (MEF2A, MEF2B, MEF2C and MEF2D) are expressed in all developmental stages of the heart 99 . More importantly, Kodo and colleagues made a sequence analysis of the MEF2C gene in 256 non-syndromic, non-familial patients with cardiac outflow tract defects, and identified a novel sequence variant (p.A103V) in a female patient with pulmonary atresia and VSD 100 .…”
Section: Discussionmentioning
confidence: 99%